(E)-4-Amino-N′-(5-chloro-2-hydroxybenzylidene)benzohydrazide - Shi, Zhong-Feng (International Union of Crystallography, 2012)
The title compound, C(14)H(12)ClN(3)O(2), displays an E conformation with respect to the C=N double bond. The dihedral angle between the benzene rings is 41.3 (5)°. The molecular structure is stabilized by an intramolecular O—H⋯N hydrogen bond. In the crystal, N—H⋯O and weak N—H⋯Cl hydrogen bonds link the molecules into a three-dimensional architecture. In addition, there are weak C—H⋯π stacking interactions.